Potential of Limestone as a Groundwater Reservoir based on Porosity Analysis in the Tintingon Area, Banggai District - Nurhikmah Supardi; Syarifullah Bundang; Meltini Pakiding (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2023)
The research area is in Tintingon Village, Banggai Regency, Central Sulawesi Province. This study aims to determine the quality of limestone as a groundwater reservoir based on porosity analysis. This study begins with sampling limestone at seven stations, then selecting fresh samples for laboratory analysis. Laboratory analysis consists of two, namely petrographic analysis and porosity analysis. The petrographic analysis aims to determine the microscopic naming of limestone and the type of pores in the rock. Porosity analysis aims to test the ability of limestone to accommodate fluids as a groundwater reservoir. Based on the petrographic analysis, it is known that the microscopic naming of limestone in the study area is wackestone and packstone. The types of limestone porosity are vug, intercrystal, channel and interparticle. Analysis of limestone porosity in the study area is known to be 15.24% - 29.95%. The porosity value is categorized as good to excellent so the research area is very good as a groundwater reservoir rock.